THE DEVELOPMENT OF GUIDED INQURY WORK SHEET FOR STUDENT WITH PHYSICS INTERACTIVESIMULATION - Yoga Budi Bhakti; Napis Napis (Jurnal Pendidikan Fisika, 2018)
This study aims to develop worksheets of student with the approach guided inquiry with physics the Interactivesimulation in learning.Who discussed subjects of material the momentum and impulses, because this material is still abstract according to high school students and still related to daily life.To overcome the problems so created learning innovation in Interactive form of media that can be pulled like let learn physics students in response.The object of this research is Interactive media based phet simulation designed in accordance with competency standard in 2013 curriculum.Research methods that were used is the method research and development, it would follow the one with the process of addie model was (analysis, design, development, implementation and evaluation). In this research, only reached the stage of development.